Audio description training: A snapshot of the current practices. Issue 1 (2nd January 2021) - Mazur, Iwona; Chmiel, Agnieszka
ABSTRACT: Audio description (AD) is a mode of audiovisual transfer which involves making audiovisual content and live performances accessible to people with sight loss. With the growing demand for this audiovisual translation (AVT) practice, a need has arisen to train professionals in the area. As a result, AD courses have sprung up, both in the form of university courses and professional in-house training. In this article we present a snapshot of the current AD training practices that were reviewed as part the ADLAB PRO project. We report on the results of a survey conducted among 86 AD trainers, involved in the delivery of a total of 192 courses. We first present some general information about the courses and the trainers, and then compare academic and non-academic courses vis-à-vis taught skills, conducted activities as well as competences and transferable skills that are deemed important. The results show that both course types are very practical and do not differ significantly. The only two statistically significant differences encountered were the group size and the importance of vocal skills. IT-related skills, such as using special software, were not prioritised in either of the two types of courses.